Предмет: Алгебра,
автор: Хулиганка69
ПОМОГИТЕ!!!
Упростите выражение:
а)(х+4)^2-7x
б)(с-1)^2-(1-2c)
в)(х-у)^2+х(у-х)
г)(а+b)^2-2b(a-b)
д)9m^2-(n-3m)^2
е)(a^2+b^2)-(a-b)^2
ж)z(5-z)+(z-5)^2
з)3u(u+2)-(u+3)^2
Ответы
Автор ответа:
0
а)х^2+8x+16-7x=х^2+x+16
б)с^2-2c+1-1+2c=c^2
в)x^2-2xy+y^2+xy-x^2=-xy+y^2
г)a^2+2ab+b^2-2ab+2b^2=a^2+3b^2
д)9m^2-(n^2-6mn+9m^2)=9m^2-n^2+6mn-9m^2=-n^2+6mn
е)a^2+b^2-a^2+2ab-b^2=2ab
ж)5z-z^2+z^2-10z+25=-5z+25
з)3u^2+6u-u^2-6u-9=2u^2-9
Похожие вопросы
Предмет: Математика,
автор: atimofeeva110
Предмет: Математика,
автор: chumnoydok
Предмет: Геометрия,
автор: end28
Предмет: Информатика,
автор: kiselevp22
Предмет: Литература,
автор: руська2